Family support for the mathematical learning of the students of the middle basic sublevel - Toala-Bailón, Rosa María; Ávila-Rosales, Francisca Margarita (International research journal of management, IT and social sciences, 2022)
Family support in learning mathematics in students who entered in 2021 has had difficulties, so this research will study the causes that caused it. The results of the research carried out through a survey of parents are shown, to investigate the responsibility of family support in the learning of sixth grade students with respect to the support provided by parents in mathematics. A classification of topics on the family support of the students was carried out in the theoretical framework, through the analysis of family support, the causes of the conceptual errors are disclosed to improve the mathematical learning of the students. The objective of this research was to determine the correlation that exists between the perception and the support provided by parents in the subject of mathematics in sixth grade students with respect to mathematical learning. The qualitative method was applied in addition to carrying out a descriptive investigation, in addition to the inductive and descriptive method. The result was that family support affects the concept of this and the need to analyze, improve and propose a teaching-learning model based on a change in which parents are involved in their children’s learning at school was observed.